IMPLIKASI LIQUIDITY, FINANCIAL LEVERAGE, DAN KINERJA LINGKUNGAN TERHADAP FINANCIAL PERFORMANCE - Augustpaosa Nariman (Universitas Kristen Krida Wacana, 2022)
This study aims to determine the impact of liquidity, financial leverage, and environmental performance on the financial performance of manufacturing companies listed in the Indonesia Stock Exchange for the year 2018-2020. The sampling technique used in this research is the purposive sampling method. There are 26 registered manufactured companies from 2018 to 2020 that meet the criteria to be sampled. The research data used was secondary data which was processed using Microsoft excel and E-views version 12. This study uses panel data regression with a fixed effect model. The results of this study indicate that financial leverage has a positive and significant effect on the financial performance, while liquidity and environmental performance have a positive and insignificant effect on the financial performance. Keywords: Liquidity, Financial Leverage, Environmental Performance, Financial Performance